Beyond the Old Dichotomies to a New History of Capitalism: An Appreciative Critique of Robert C.H. Sweeny - MCKAY, IAN (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2017)
Robert C.H. Sweeny’s Why Did We Choose to Industrialize? offers readers enlightening quantitative case studies of the socio-economic history of nineteenth-century Montreal, linked by intriguing autobiographical sketches charting the author’s own intellectual journey. In this appreciate critique, I raise questions about the extent to which he has convincingly situated Montreal in the famous matrix of debates among Marxists about the transition from feudalism to capitalism, and suggest that in many respects the book, although convincing in many of its particulars, does not succeed in answering the general question posed by its title. Should debates about capitalism remain trapped in the unresolved (and likely unresolvable) twentieth-century debates pitting agency against structure?